STUDY ON APHRODISIAC ACTIVITY OF OLEA DIOICA ROXB. BARK, LEAF EXTRACTS, AND ITS PURE COMPOUND USING WISTAR ALBINO RATS - R, Ashwathanarayana; Naika, Raja (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objectives: We aimed to assess the effects of O. dioica Roxb. leaf and bark extract and its isolated constituent benzeneethanol, 4-hydroxy- on aphrodisiac activity in rats using different standard aphrodisiac parameters. Methods: To determine the aphrodisiac activity several parameters were observed. These include measuring and observing the mount frequency (MF), mount latency (ML), intromission frequency (IF), intromission latency (IL), anogenital sniffing (AS), and genital grooming (GG). Results: The aphrodisiac activity of O. dioica Roxb. leaf and bark extracts and its pure compound were studied on Wistar albino rats at different dosages. The parameters observed during the study were MF, ML, IF, IL, AS, and GG. The results revealed that the crude extracts showed dose-dependent activity in all the concentration, in that, ethanolic leaf extract showed excellent activity compared to ethanolic bark extract and pure compound benzene ethanol 4-hydroxy. Conclusion: Results showed the excellent aphrodisiac activity of O. dioica Roxb. leaf and bark ethanolic extracts. However, the major compound benzeneethanol, 4-hydroxy- was not responsible for the aphrodisiac activity, may be the minor compounds even though in minor concentration in the extract influence the sexual activity in tested animals.